A functional analysis of text-oriented formulaic expressions in written academic discourse: Multiword sequences vs. single words. (April 2019) - Wang, Ying
Abstract: Text-oriented formulaic expressions (e.g., in addition to, on the other hand, nevertheless ) are important in crafting reader-friendly prose and particularly frequent in academic discourse. By accommodating both multi-word expressions (MWEs) and single-word expressions (SWEs), the present study is among the first attempts to explore how the two types of expressions relate and contribute to the level of formulaicity in academic discourse. Through a manual examination of formulaic expressions in context, the present study provides important insights into the nature of formulaicity in the organisation of written academic discourse produced by mature and developing writers, with pedagogical implications for the training of novice writers in scientific fields. Highlights: The study focuses on textual expressions in academic discourse. Formulaic sequences are manually identified and annotated. Some textual functions tend to be realised by MWEs and some by SWEs. Expert writers employ more MWEs whereas novices rely heavily on SWEs. Expressions with multiple functions need more attention in EAP pedagogy.